Coastal upwelling and redox variations in the northwestern Tarim Basin (northwest China) during the Middle-Late Ordovician: implication for paleo-depositional conditions of the organic matter enrichment in the Saergan Formation - Zhu, Bi; Guo, Tingting; Liu, Chenhui; Pan, Wenqing; Chen, Yongquan; Zhang, Yinggang; Yang, Tao (Frontiers in Earth Science, 2023)
The black shales of the Saergan Formation, which represent one of the main hydrocarbon source rocks in the Tarim Basin, witnessed a time span of organic matter enrichment by profound changes in the Earth System. A multi-proxy geochemistry study was carried out on the samples of the Saergan Formation to reconstruct the depositional environment and to explore the mechanism of organic matter enrichment of the unit at the Yingshanbeipo section, Keping area, northwest Tarim. Elemental and TOC data are suggestive of an upwelling setting, with a less pronounced oxygen minimum zone (OMZ) compared to the highly productive Peru and Namibian margins. Ferruginous anoxic bottom water conditions prevailed during most time of the deposition, with suboxic conditions dominating the basal and the top parts of the studied unit. As a whole, primary productivity seems to be the dominating factor that controlled the micronutrients and OM accumulations in the Saergan Formation whereas the role of benthic redox conditions may have been subordinate. The variations in primary productivity and bottom water redox conditions were resulted by the multiple, interacting environmental factors including nutrient supply regulated by oceanic circulation and climate changes, and relative sea-level fluctuations.